Accessibility, Usability and User Experience Design for Visually Impaired People: A Systematic Mapping Study - Rosa, João Ricardo dos Santos; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
The use of Information and Communication Technologies (ICTs) can be an important ally in improving the quality of life of Visually Impaired People (VIP) because they provide greater independence in the performance of their daily tasks. During the development process of ICTs for VIP, the concepts of Accessibility, Usability, and User eXperience (UX) are significant because they can positively influence the system’s quality. Concerning these concepts, some improvements can be considered already at the design stage, such as screen size, button format, color density, among others. However, not all designers consider Accessibility, Usability, and UX concepts when designing ICT for VIP. To identify and characterize which design technologies of Accessibility, Usability, and UX have been proposed in the literature, we performed a Systematic Mapping Study (SMS). We identified a total of 23 technologies. The analysis from these technologies showed that the majority are destined for mobile applications. Besides, some design technologies only address the concept of Accessibility, and only one technology considered the concepts of Accessibility, Usability, and UX together. To support professionals, students, and researchers in Human-Computer Interaction (HCI) and Software Engineering (SE), this SMS presents a set of Accessibility, Usability, and UX design technologies, which can be used in the initial phases of the ICT development process for VIP.